Multi-Energy Cooperative Primary Frequency Regulation Analysis of a Hybrid Plant Station for Wind Power and Hydrogen Production Based on Ensemble Empirical-Mode Decomposition Algorithm - Dongyang Sun; Jixuan Yu; Wenyuan Zheng; Junlin Ruan; Guangxin Zu (Applied Sciences, 2023)
Wind curtailment and inadequate grid-connected frequency regulation capability are the main obstacles preventing wind power from becoming more permeable. The electric hydrogen production system can tackle the wind curtailment issue by converting electrical energy into hydrogen energy under normal operating circumstances. It can be applied as a load-reducing method during frequency regulation to help the system restore the power balance. First, this study proposes the concept of a hybrid plant station that combines the production of hydrogen and wind energy. This plant station will be referred to as a hybrid station with centralized hydrogen production and distributed energy storage. By mimicking the synchronous generator’s frequency control features, the primary frequency regulation mechanism of a hybrid plant station is examined. Secondly, due to the frequency regulation requirements of the power grid’s full-time domain hybrid power station, this paper proposes a hybrid plant station control strategy based on the EEMD variable parameter control algorithm. In frequency regulation power, the electric hydrogen production device load reduction responds to the low-frequency component, and the supercapacitor responds to the high-frequency component. The impact of the dynamic characteristics of alkaline electrolyzers on the frequency regulation effect is analyzed in this article, along with a comparison of the matching of various energy storage devices and electrolyzers in power grid frequency regulation. Finally, the feasibility and soundness of the proposed control strategy are confirmed by creating a simulation model representing a hybrid plant station involved in primary frequency management under various operational scenarios.